2017
DOI: 10.1155/2017/7158756
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Essential Oils against Candida albicans Strains Isolated from Users of Dental Prostheses

Abstract: Objective The objective of this study was to analyze the antifungal activity of citral, selected by screening natural products, against Candida albicans isolates from subjects who use dental prostheses. Methodology Screening of essential oils, including those from Mentha piperita L. (Briq), Origanum vulgare, and Zingiber officinale L., and the phytoconstituents citral and limonene, to select an appropriate natural product. Citral, which mediated the best antifungal response, was selected for biological assays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…The test was performed in duplicate and the means of the values obtained were used to classify the bacterium as sensitive (� 10 mm) or resistant (< 10 mm) [25]. The MIC of CCeo and trans-cinnamaldehyde (TC) were determined by broth microdilution, as described by Cavalcanti et al [26] and was determined by resazurin colorimetric assay. CCeo was diluted with distilled water and 0.5% Tween-80.…”
Section: Antibacterial Assays Of Cceomentioning
confidence: 99%
“…The test was performed in duplicate and the means of the values obtained were used to classify the bacterium as sensitive (� 10 mm) or resistant (< 10 mm) [25]. The MIC of CCeo and trans-cinnamaldehyde (TC) were determined by broth microdilution, as described by Cavalcanti et al [26] and was determined by resazurin colorimetric assay. CCeo was diluted with distilled water and 0.5% Tween-80.…”
Section: Antibacterial Assays Of Cceomentioning
confidence: 99%
“…Previous studies on the antimicrobial activity of limonene, revealed its strong anti-C. albicans activity and their mode of action. [12] The antifungal activity of linalool was comparable to that of verbenone. Published reports on the effectiveness of linalool on clinical isolates of C. albicans supported the weak inhibitory effects found in the present investigation.…”
Section: Yields and Chemical Profilingmentioning
confidence: 93%
“…Strains ATCC-76485 and LM-4b were used to evaluate possible changes in the micromorphology of C. albicans cells exposed to isoeugenol. In this assay, microcultures were performed in a humid chamber using solid agar-cornmeal-Tween 80 (Difco ® , Sparks, MD, USA) [ 16 ]. Aliquots of 3 mL of liquid agar-cornmeal-Tween 80, homogenized with MIC, MIC × 2 and MIC × 4 of the test products, were poured into a glass slide and C. albicans were seeded and incubated at 35 °C ± 2 °C for 24–48 h.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, medicinal plants represent a vast source of new pharmacologically active molecules for the treatment of fungal diseases [ 15 , 16 , 17 ]. Among the compounds isolated from plants, phenylpropanoids constitute a group of phytoconstituents derived from phenylalanine widely found in essential oils such as Syzygium aromaticum (clove), Myristica frangrans (walnut shown), Ocimum basilicum (basil) and Laurus nobilis (louro) oils [ 15 , 18 , 19 , 20 ], with isoeugenol being a representative of this class of molecules [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%